Assessing travel motivations, satisfactions and branding success in heritage tourism: Fang Gu Jie in Chengdu, Sichuan - Schuessler, Fabien (fi=Turun yliopisto|en=University of Turku|, 2017)
Domestic tourism in China has grown exponentially since 1980 with important consequences for heritage preservation efforts, heritage commercialisation and urban branding goals amidst stronger inter-urban competition in capitalising China. Reconstructed historic areas are increasingly developed into commercial tourist destinations for urban branding and attracting tourists, known as Fang Gu Jie. Branded as important historic centres of and heritage sites, their reality is mainly focused on food, shopping and sightseeing closer to a theme park than a heritage site. This thesis examines if branding efforts have reached tourists, which factors motivated them to visit and how satisfied they feel after. A quantitative survey study was conducted in Chengdu, Western China regarding its three main Fang Gu Jie areas, accompanied by qualitative observation results. It found a growing development towards heritage, history and culture in travel motivations among Chinese tourists as well as significant criticism regarding insufficient heritage authenticity at the sites, yet overall levels of satisfaction with their visits. There was also an evident link between participant’s region of origin, income levels as well as age. Lastly, the study showed how Fang Gu Jie sites are widely known in contemporary Chinese society, explaining their wide success, thanks to their commercial and touristic nature.